THE VALUE OF IḤTIYĀṬ’S PRAYER TIMES IN SEMARANG CITY - Maulana, Muhammad Irkham (Al-Hilal: Journal of Islamic Astronomy, 2024)
The prayer schedule is usually applied to one area, such as Semarang City, considering the existing area, its area, and its height. The value of iḥtiyāṭ certainly has a role in implementing prayer times to accommodate all parts of one area as well as a safety measure against miscalculations; the method is carried out by taking into account prayer times in the eastern and the westernmost regions, as well as lowland and highland areas, then compared to the reference prayer time, in this case, the Great Mosque of Central Java. For the city of Semarang, with an east-west area of 24.2 km and an altitude of 0-405 meters above sea level, it is safe to use an iḥtiyāṭ of 2 minutes. However, considering the highland areas, it is necessary to use an iḥtiyāṭ value of 3 minutes for maghrib and evening prayer times.